PERANCANGAN SISTEM SELEKSI PETUGAS SENSUS PENDUDUK MENGGUNAKAN METODE PROFILE MATCHING - Anisya Sonita; Ika Yurika Sari (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
Population census is the whole process of enumerating, compiling, tabulating and publishing demographic data. The Central Statistics Agency (BPS) is an institution that carries out these activities, one of which is the Bengkulu City Statistics Agency. The problem in this study is that the final decision-making process is still carried out manually by selecting one by one candidate for census officers and there is no special system that can provide mathematical census officer selection results. The purpose of this study, which is to create a decision support system that can help to select candidates or candidates for population census officers using the profile matching method. The profile matching method is used to compare the candidate's profile with the profile required by the position to be filled. In this study, the selection system using the profile matching method can be used as a system to facilitate the selection process of prospective population census officers. This is evidenced in the percentage results obtained after going through the calculation of all values by getting a result of 84.4%, with results that are considered to have met the feasibility according to the interpretation of the score. The objectives of this research are considered to have been achieved, given the level of accuracy and percentage that has been obtained and has been proven.